Treaty on Prohibition of Nuclear Weapons: Position, implementation and significance - Arsić Katarina (Srpska Politička Misao)
Although there was a opinion that the Treaty on Prohibition of Nuclear Weapons would represent the end of the era of the development of this type of weapon and the threat of nuclear war, this did not happen, having in mind that no country possessing a nuclear arsenal have acceded to the Treaty yet. The paper analyzes the main aspects of this document, its advantages and disadvantages. Additionally, using a comparative method, we will try to determine the relationship of this treaty with other sources of international public law, primarily treaties that may refer to the use of nuclear weapons, but also customs. Special attention is given to the influence of the Advisory Opinion of the International Court of Justice on the legality of the use of nuclear weapons on the attitudes of states on the permissibility of the use of nuclear weapons. At the end, taking into account the current political and social circumstances in international relations and the opinions of international law theorists, we will try to answer the question why this treaty is still important, because nuclear weapons are the tool may be played by nuclear powers, especially in terms of their potential use in the case of self-defence.